Hyperactive transposase mutants of the Himar1 mariner transposon - Lampe, David J. (The National Academy of Sciences, 1999)
Mariner-family transposable elements are active in a wide variety of organisms and are becoming increasingly important genetic tools in species lacking sophisticated genetics. The Himar1 element, isolated from the horn fly, Haematobia irritans, is active in Escherichia coli when expressed appropriately. We used this fact to devise a genetic screen for hyperactive mutants of Himar1 transposase that enhance overall transposition from ≈4- to 50-fold as measured in an E. coli assay. Purified mutant transposases retain their hyperactivity, although to a lesser degree, in an in vitro transposition assay. Mutants like those described herein should enable sophisticated analysis of the biochemistry of mariner transposition and should improve the use of these elements as genetic tools, both in vivo and in vitro.